The Attitudes towards ICT and the Internet Usage of Teachers of Secondary Education: Case in TRNC - Soyşen, Ekrem (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The research study examined the attitudes towards Information and Communication Technology (ICT) and the internet usage of the teachers of secondary education in the case of TRNC. In this research, data adopted was gathered via both quantitative and qualitative method. For collecting data via quantitative method, a questionnaire instrument is distributed to the selected 252 teachers of secondary education. In addition, interview method was also adopted during the collection of data phase, by administering a purposive interview questions to 25 teachers in order to elicit useful responses regarding to their attitudes towards ICT and internet usage. Analysis was carried out on gathered data using ANOVA, t-test, standard deviations and percentages. Significant differences were also conducted on the variable factors based on the demographic characteristics of each participant. The findings of this study showed that, majority of the respondents hold a high response on their attitudes towards ICT and also have higher responses in their level of the internet usage. Moreover, it was also observed that there is no significant difference between the male and the female respondents' attitudes toward ICT tools and level of internet usage. It is worth to mentioned that, the analyzed data showed that no significant difference exists regarding to the teachers' attitudes towards ICT and their level of internet usage whether the teachers have attended any computer classes or not, participated to a computer certificate or not, their years of experiences and the purpose of their daily computer usage. Keywords: Information and Communication Technology, Internet usage, secondary education, teachers' attitudes

ÖZ : Araştırma çalışması, KKTC’deki ortaöğretim öğretmenlerinin “ Bilgisayar ve İletişim Teknolojilerine” (BİT)’e ve internet kullanım düzeylerine yönelik tutumlarını incelemektedir. Bu araştırmada, benimsenen veriler hem nicel hem de nitel yöntemle toplanmıştır. Nicel yöntemle veri toplamak için bir anket aracı, seçilen 252 ortaöğretim öğretmenine dağıtılmıştır. Buna ek olarak, ortaöğretim öğretmenlerinin BİT ve internet kullanımına yönelik tutumları üzerinde detaylı bilgi toplayabilmek için 25 öğretmene ise mülakat soruları verilmiştir. Çalışma analizi, Anova, t-testi, standart sapma ve yüzde kullanılarak toplanan veriler üzerinde yürütülmüştür. Her katılımcının demografik özellikleri dikkate alınarak, çeşitli değişken faktörler üzerinde tutumlarına yönelik göstermiş oldukları önemli farklılıkları incelenmiştir. Bu çalışmanın bulguları, katılımcıların, BİT’e ve internet kullanım düzeylerine yönelik yüksek tepkilerinin var olduğunu göstermiştir. Ayrıca, kadın ve erkek katılımcıların BİT araçlarına ve internet kullanım seviyesine karşı tutumları arasında anlamlı bir fark olmadığı gözlenmiştir. Buna ek olarak çalışmada, öğretmenlerin BİT’e ve internet kullanım düzeylerine yönelik tutumlarında da herhangi bir bilgisayar kursuna katılıp katılmadıkları, bilgisayar kullanım sertifikalarının olup olmadığı, tecrübelerinin ve günlük bilgisayar kullanım amaçlarının, tutumları üzerinde herhangi bir önemli farklılık göstermediği gözlemlenmiştir. Anahtar Kelimeler: Bilgi ve İletişim Teknolojileri, İnternet kullanımı, ortaöğretim, öğretmenlerinin tutumları
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technologies in Education, 2016. Supervisor: Dr. Fatma Tansu Hocanın.
Keywords: Information and Communication Technologies in Education; Information and Communication Technologies in Education-Higher Education-Cyprus, North; Instructor Attitudes-Teachers Attitudes-Information Communication Technologies; Education - Computer network resources; Educational Technology-E-Learning; Teaching-Computer Network Resources